2018
DOI: 10.1186/s12933-017-0652-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cardiac microvascular dysfunction measured with 82Rubidium-PET and albuminuria in patients with diabetes mellitus

Abstract: BackgroundAlbuminuria is of one the strongest predictors of cardiovascular disease (CVD) in diabetes. Diabetes is associated with cardiac microvascular dysfunction (CMD), a powerful, independent prognostic factor for cardiac mortality. The aim of this study was to evaluate the relationship between CMD and microvascular complications in patients without known CVD.MethodsIn this monocentric study, myocardial flow reserve (MFR) was measured with cardiac 82Rubidium positron emission tomography (Rb-PET) in 311 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Our findings are consistent with a recent observational study using Positron Emission Tomography by Potier et al 22 who demonstrated that micro-and macroalbuminuria in T2DM were associated with a three-and eight-fold increased risk of impaired MPR respectively, even after adjustment for known cardiovascular confounders. Interestingly, this previous study showed no difference in MPR between control subjects and normoalbuminuric patients with T2DM which contrasts the findings in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with a recent observational study using Positron Emission Tomography by Potier et al 22 who demonstrated that micro-and macroalbuminuria in T2DM were associated with a three-and eight-fold increased risk of impaired MPR respectively, even after adjustment for known cardiovascular confounders. Interestingly, this previous study showed no difference in MPR between control subjects and normoalbuminuric patients with T2DM which contrasts the findings in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Both endothelial-dependent and -independent CMD are linked to ischemia [14, 15], and thus CMD could represent the underlying mechanism for angina in diabetics who have non-obstructive CAD at angiography. Studies have also shown that systemic microvascular abnormalities may involve endothelin-1 and are common in patients with microvascular angina [18], while others have shown that impaired myocardial flow reserve, which leads to angina, is frequent in type 2 diabetics, and is strongly associated with the degree of albuminuria [19]. These findings suggest that CMD and albuminuria might share common mechanisms, and underscores the notion that microvascular disease in diabetes is a systemic phenomenon extending beyond ‘known’ microvascular beds such as the kidneys and into the coronary circulation.…”
Section: Discussionmentioning
confidence: 99%
“…CMD is clinically meaningful as it mediates ischemia leading to angina [14, 15] and is associated with an increased risk of cardiovascular events [16, 17]. Studies have shown that systemic microvascular abnormalities may involve endothelin-1, which is common in patients with microvascular angina [18], while others have shown that impaired myocardial flow reserve is frequent in type 2 diabetics, and is strongly associated with the degree of albuminuria [19]. CMD and albuminuria may therefore share common mechanisms related to the pathogenesis of diabetic micro-vasculopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing diabetes prevalence will lead to increasing the side effects of this disease as well as patient’s morbidity and mortality. Diabetes is accompanied with 2 to 4 times increased risk of the CAD development and progression (14). The mortality resulted from any cause including CAD likely will be more in younger patients who have also higher serum glucose levels and suffer from diabetic nephropathy (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Potier et al (14) assessed the correlation between cardiac microvascular dysfunction and microalbuminuria in diabetics with 82 Rubidium-positron-emission tomography scan. In their study, myocardial flow reserve (MFR) was significantly lower in diabetic patients versus non-diabetics.…”
Section: Discussionmentioning
confidence: 99%